Adventure travel and the COVID-19 pandemic — recommendation of the Medical Commission of the Union Internationale des Associations d’Alpinisme (UIAA) - Szawarski, Piotr; Hillebrandt, David (Health Promotion & Physical Activity, 2021)
Lots of information is available by news, internet, social media, press and medical papers. However there is a lack of specific information on how to manage the COVID risk while mountaineering. The paper should assist mountaineers and agencies to fulfill safety procedures en route.